Thermal behavior and failure mechanisms of 18650 lithium ion battery induced by overcharging cycling - Huaiyu Zhong; Qingdong Zhong; Jian Yang; Shengwen Zhong (Energy Reports, 2022)
Overcharging is one of the most serious safety problems in large-scale application of lithium ion battery (LIB). An in-depth understanding of the failure mechanism of battery overcharge is necessary to guide the safe design of battery system. In this paper, the electrochemical performance of commercial 18650-type cylindrical battery with Li(Ni0.5Co0.2Mn0.3)O2 cathode and graphite anode as the background is evaluated with different state of charge (SOC). The dynamic thermal behavior of overcharge in adiabatic conditions is studied, and the cathode materials, separator and anode materials after long-term overcharge cycle are characterized to identify the side reactions in battery. The results show that the battery impedance increases with the increase of SOC, and thereby greatly accelerating the attenuation of battery capacity. When LIB is charged and discharged in adiabatic conditions, the battery surface temperature of 116% SOC is about 10.03 °C higher than that of 100% SOC. Therefore, the battery with higher SOC has higher heating and is easy to induce the thermal runaway reactions. During the overcharge cycle, electrolyte decomposition, transition metal dissolution and phase transformation occur at the cathode, and serious lithium plating occur at the anode, as a result, increasing battery impedance, accelerating aging and increasing heat production. These results provide feasible support for understanding the overcharge mechanism and battery management system.